Rhino-Orbital-Cerebral Mucormycosis in a Post-COVID-19 Patient from Peru - Linda Ponce-Rosas; Jose Gonzales-Zamora; Nelson Diaz-Reyes; Oliver Alarco-Cadillo; Jorge Alave-Rosas (Case Reports in Infectious Diseases)
Mucormycosis has been reported increasingly in patients affected by COVID-19, especially in India where the first cases were described. In Latin America, there is limited information about this association, mainly coming from Brazil, Mexico, and Peru. Herein, we report the case of a 66-year-old female that presented with rhino-orbital-cerebral mucormycosis, diabetic ketoacidosis, and COVID-19. The patient had the compromise of all the sinuses, orbital invasion, and intracranial extension. Isavuconazole was promptly initiated because amphotericin B was not available. She had a single open surgical debridement of necrotic tissues at the beginning of the diagnosis then multiple manual sessions to clear the residual or recurrent disease during approximately 5 months. Isavuconazole was effective and well-tolerated for 10 months without side effects. We highlight the importance of considering mucormycosis in post-COVID-19 patients with uncontrolled diabetes. The report emphasizes the favorable outcome of isavuconazole as an alternative therapy.